2012
DOI: 10.1111/j.1528-1167.2012.03604.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of psychiatric and seizure outcome following temporal lobe epilepsy surgery

Abstract: SUMMARYPurpose: Neurosurgery is an effective therapy for selected individuals with medically refractory temporal lobe epilepsy (TLE). De novo psychopathology may complicate the postsurgical outcome. Our aims were to identify predictors of de novo psychiatric and seizure outcome following TLE surgery. Methods: Medical records of 280 patients who underwent TLE surgery were reviewed. Preoperative and postoperative psychiatric diagnoses were identified, in addition to information on seizure recurrence and neuropsy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
59
2
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(65 citation statements)
references
References 39 publications
(58 reference statements)
0
59
2
4
Order By: Relevance
“…15) The present and previous findings have implicated TLE and presurgical psychiatric history as important risk factors for postoperative psychiatric problems. 1,5,9,14) In contrast to the present results, some earlier studies identified poor seizure outcome and surgical side as strong predictive factors. 1,2,15) The findings of the types of postoperative disorders have also varied: earlier papers more commonly report milder psychiatric issues 9) and transient mood disorders such emotional lability and depression, 5) whereas we predominately observed conditions requiring treatment with antipsychotic drugs.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…15) The present and previous findings have implicated TLE and presurgical psychiatric history as important risk factors for postoperative psychiatric problems. 1,5,9,14) In contrast to the present results, some earlier studies identified poor seizure outcome and surgical side as strong predictive factors. 1,2,15) The findings of the types of postoperative disorders have also varied: earlier papers more commonly report milder psychiatric issues 9) and transient mood disorders such emotional lability and depression, 5) whereas we predominately observed conditions requiring treatment with antipsychotic drugs.…”
Section: Discussioncontrasting
confidence: 99%
“…1,5,9,14) In contrast to the present results, some earlier studies identified poor seizure outcome and surgical side as strong predictive factors. 1,2,15) The findings of the types of postoperative disorders have also varied: earlier papers more commonly report milder psychiatric issues 9) and transient mood disorders such emotional lability and depression, 5) whereas we predominately observed conditions requiring treatment with antipsychotic drugs. The follow-up period and patient selection criteria might partly explain these discrepancies, as our subgroup of patients with postoperative psychiatric disorders was limited to patients who received psychotropic drugs 2 or more years after the surgery.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In one previous study of 116 consecutive patients who had temporal lobe surgery for drug-resistant epilepsy and MTS 9 , the occurrence of generalized tonic-clonic seizures was significantly associated with a poor outcome. In another study of 280 patients who underwent TLE surgery 7 , patients with a history of generalized tonic-clonic seizure(s) were significantly less likely to remain seizure free (odds ratio 0.47, 95% CI 0.25-0.90, p = 0.02).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are still uncertainties about which patients will benefit most [3][4][5][6] . One of the most consistent risk factors associated with poor outcome after surgery for drug-resistant TLE in the literature is a history of preoperative tonic-clonic seizures [6][7][8][9] . However, no investigators have defined what is meant by the presence of tonic-clonic seizures.…”
Section: Introductionmentioning
confidence: 99%